Bacteria Respond Stronger Than Fungi Across a Steep Wood Ash-Driven pH Gradient - Cruz-Paredes, Carla; Bang-Andreasen, Toke; Christensen, Søren; Ekelund, Flemming; Frøslev, Tobias G.; Jacobsen, Carsten Suhr; Johansen, Jesper Liengaard; Mortensen, Louise H.; Rønn, Regin; Vestergård, Mette; Kjøller, Rasmus (Frontiers in Forests and Global Change, 2021)
Soil pH is probably the most important variable explaining bacterial richness and community composition locally as well as globally. In contrast, pH effects on fungi appear to be less pronounced, but also less studied. Here we analyze the community responses of bacteria and fungi in parallel over a local extreme pH gradient ranging from 4 to 8. We established the pH gradient by applying strongly alkaline wood ash in dosages of 0, 3, 9, 15, 30 and 90 t ha-1 to replicated plots in a Picea abies plantation and assessed bacterial and fungal community composition using high throughput amplicon sequencing one year after ash application. At the same time, the experiment investigated if returning wood ash to plantation forests pose any immediate threats for the microbial communities. Among the measured environmental parameters, pH was by far the major driver of the microbial communities, however bacterial and fungal communities responded differently to the pH increment. Whereas both bacterial and fungal communities showed directional changes correlated with the wood ash-induced increase in pH, the bacterial community displayed large changes at wood ash dosages of 9 and 15 t ha-1 while only higher dosages (>30 t ha-1) significantly changed the fungal community. The results confirm that fungi are less sensitive to pH changes than bacteria but also that fertilizing plantation forests with wood ash, viewed through the lens of microbial community changes, is a safe management at standard dosages (typically 3 t ha-1).